Effect of Age, Sex, and Postural Alignment on Dynamic Balance in Older Adults - Rosyada, Itsna; Saraswati, Elsa Verina; Khasanah, Fahrun Nisa Sofiyah (Oshada, 2026)
Dynamic balance has been widely associated with fall risk among older adults and is commonly positioned as a predictor of fall events. However, its role as an indicator of functional mobility quality has received comparatively less attention. In addition, chronological age and sex are frequently considered in the evaluation of mobility performance, even though it does not always accurately represent an individual’s actual functional condition. This study aimed to examine the associations of age, sex, and postural alignment with dynamic balance among community-dwelling older adults. An analytical observational study with a cross-sectional design was conducted involving 28 older adults attending a community elderly health post in Bangunrejo, Kricak, Tegalrejo, Yogyakarta. From all individuals who met the initial inclusion criteria, only participants with complete data were included in the final analysis. Age and sex were recorded as demographic characteristics, postural alignment was assessed using the Reedco Posture Score, and dynamic balance was evaluated using the Timed Up and Go (TUG) test. Data analysis was performed using Spearman’s correlation. The results showed that age (ρ = 0.207; p = 0.291) and sex (ρ = −0.111; p = 0.575) were not significantly associated with TUG performance. In contrast, postural alignment demonstrated a significant negative association with TUG time (ρ = −0.411; p = 0.030), indicating that better postural quality was related to superior functional mobility. This study concludes that, among community-dwelling older adults, dynamic balance more strongly reflects functional condition influenced by postural alignment rather than demographic factors, highlighting the importance of simple functional assessments in the evaluation of mobility in older populations.